Bryostatin-1 enhances the proliferation and functionality of exhausted CD8+ T cells by upregulating MAP Kinase 11 - Li, Ling; Zhao, Manzhi; van Meurs, Marjan; Brouwers-Haspels, Inge; den Dekker, Renske J. H.; Wilmsen, Merel E. P.; Grashof, Dwin G. B.; van de Werken, Harmen J. G.; Rao, Shringar; Rokx, Casper; Mueller, Yvonne M.; Katsikis, Peter D. (Frontiers in immunology, 2025)
Bryostatin-1, a potent agonist of the protein kinase C, has been studied for HIV and cancer therapies. In HIV research, it has shown anti-HIV effects during acute infection and reactivation of latent HIV in chronic infection. As effective CD8+ T cell responses are essential for eliminating reactivated virus and achieving a cure, it is important to investigate how bryostatin-1 affects HIV-specific CD8+ T cells. HIV-specific CD8+ T cells often become exhausted, showing reduced proliferative potential and impaired cytokine production, a dysfunction also observed in cancer. Therefore, we further investigated how bryostatin-1 directly impacts exhausted CD8+ T cells. PBMCs from people with HIV (PWH) were treated with bryostatin-1 and tracked with proliferation dye for cell expansion. One day 6, HIV-specific CD8+ T cells were detected by tetramers staining and examined by flow cytometry. By utilizing an established murine T cell exhaustion system, changes in inhibitory receptors, transcription factors, cytokine production and killing capacity of bryostatin-1 treated exhausted CD8+ T cells were determined by flow cytometry. RNA-seq analysis was performed to study transcriptional changes in these cells. We found that bryostatin-1 improved the expansion and decreased PD-1 expression of HIV-specific CD8+ T cells. Bryostatin-1 enhanced the functionality and proliferation while decreasing inhibitory receptor expression of generated exhausted CD8+ T cells. Bryostatin-1 upregulated TCF-1 and decreased TOX expression. These changes were confirmed through RNA-seq analysis. RNA-seq revealed that mitogen-activated protein kinases (MAPK) 11 was significantly downregulated in exhausted CD8+ T cells, however, it greatly upregulated after bryostatin-1 treatment. Inhibition of MAPK11 in bryostatin-1-treated cells blocked the increased proliferation and IFN-γ production induced by bryostatin-1, but did not affect other bryostatin-1 induced effects, such as the reduction of inhibitory receptors. Our data demonstrate that bryostatin-1 induces a MAPK 11-dependent improvement in the proliferative and functional capacity of exhausted T cells. This study provides a rationale for bryostatin-1's potential to help eradicate the HIV reservoir during treatment, and it may also contribute to cancer immunotherapy by functionally improving exhausted CD8+ T cells.